Impact of internal oversight on transparent performance in educational institutions - Alataiwi, Mohammed Hamdan (Journal of Educational and Psychological Sciences, 2022)
The purpose of the study was to identify the role of internal control in achieving transparency in the performance of educational institutions. The study was applied to the education directorates of the Northern Aguar Brigade. In order to achieve the objective of the study, the design of the resolution study tool was followed. It was confirmed that it was true and stable. (40) a staff member of the Education Directorates of the Northern Aguar Brigade of the Hashemite Kingdom of Jordan, selected in a deliberate manner. The results of the study are as follows: The general estimate of the study sample on the impact of internal control on the transparency of performance in educational institutions has received a total average. In the light of the results of the study, the researcher made a number of recommendations, including awareness-raising among personnel in educational institutions, in order to clarify the basis for building transparency and dimensions in order to be an active supporter of the implementation of internal control objectives through workshops and demonstration seminars.